A food demand system based on demand for characteristics: if there is ' curvature' in the Slutsky matrix, what do the curves look like and why? - Bouis, Howarth E. (Elsevier, 1996)
This article develops a food demand system based on the demand for energy, variety, and tastes of foods. It specifies utility as a function of those characteristics and uses them to derive demand elasticities that explain why the poor are particularly responsive to food prices.